Effects of adult education on cognitive function and risk of dementia in older adults: a longitudinal analysis - Takeuchi, Hikaru; Kawashima, Ryuta (Frontiers in Aging Neuroscience, 2023)
Mid/late-life cognitive activities are associated with lower rate of subsequent cognitive decline and lower subsequent dementia risk over time. In this study, we investigated the association between adult education class participation and subsequent cognitive decline and dementia risk over time after adjusting for baseline cognitive function and genetic risk of dementia, correcting for several potential confounding variables, using a large prospective cohort data of participants from the UK Biobank study followed from 2006 to 2010. The results revealed that participation in adult education classes at baseline was associated with greater subsequent retention of fluid intelligence score. Cox proportional hazard models revealed that subjects who participated in adult education classes showed a significantly lower risk of incident dementia five years after baseline compared with those that did not at baseline. Together, in this study, we show that participation in adult education classes preceded greater retention of subsequent fluid intelligence and a lower risk of developing dementia after five years; this association did not change after adjusting for cognitive function at baseline or genetic predisposition to dementia. Accordingly, participation in such classes could reduce the risk of developing dementia.